2013
DOI: 10.1103/physreve.88.020401
|View full text |Cite
|
Sign up to set email alerts
|

Rotation-induced grain growth and stagnation in phase-field crystal models

Abstract: We consider grain growth and stagnation in polycrystalline microstructures. From the phase-field crystal modeling of the coarsening dynamics, we identify a transition from a grain-growth stagnation upon deep quenching below the melting temperature T(m) to a continuous coarsening at shallower quenching near T(m). The grain evolution is mediated by local grain rotations. In the deep quenching regime, the grain assembly typically reaches a metastable state where the kinetic barrier for recrystallization across bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Among the many quasi-classical methods for treating the nonadiabatic nuclear dynamics, e.g., the semiclassical initial-value representation (IVR) [12][13][14][15] , the Ehrenfest dynamics method [16][17][18][19][20] , the frozen Gaussian wavepacket method 21 , the multiple-spawning wave-packet method [22][23][24][25] , to mention a few, the classical trajectory surface-hopping method with its many variants [26][27][28][29][30][31][32][33][34][35][36][37][38][39] is one of the most widely used mixed quantum-classical computational methods.…”
Section: Introductionmentioning
confidence: 99%
“…Among the many quasi-classical methods for treating the nonadiabatic nuclear dynamics, e.g., the semiclassical initial-value representation (IVR) [12][13][14][15] , the Ehrenfest dynamics method [16][17][18][19][20] , the frozen Gaussian wavepacket method 21 , the multiple-spawning wave-packet method [22][23][24][25] , to mention a few, the classical trajectory surface-hopping method with its many variants [26][27][28][29][30][31][32][33][34][35][36][37][38][39] is one of the most widely used mixed quantum-classical computational methods.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to classical grain growth laws, grain growth are also known to stagnate in time 10 . In two dimensional systems, it has been suggested that the stagnation might be a combination of high kinetic barriers, preventing mass migration across grain boundaries, and a locking of individual grains preventing grain rotation and subsequent lattice alignment 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The reasons being trifold: (a) Computing their ab-initio values was always considered as being difficult; [8,9] (b) Even having explicit mathematical expressions for the NACTs, the fact they were frequently singular (see Equation (1)), they had to be eliminated from the relevant Schrödinger equation (see, below, Equation (3)). This process introduced further difficulties; (c) The introduction of the (successful) semi-classical trajectory-surface-hopping (TSH) approach [10][11][12][13][14] became the more popular way to study charge transfer (CT) processes an approach that to a certain level avoids the NACTs.…”
Section: Background Informationmentioning
confidence: 99%